Thermomechanical processing route to achieve ultrafine grains in low carbon microalloyed steels. (15th October 2016) - Gong, P.; Palmiere, E.J.; Rainforth, W.M.
Abstract: A new thermomechanical processing route is described for a microalloyed steel, with roughing deformation below the recrystallisation-stop temperature (T5% ), followed by a rapid reheat to 1200 °C for 10s, and then finish deformation at the same temperature as the rough deformation. The new route focused on optimising the kinetics of strain-induced precipitation (SIP) and the formation of deformation-induced ferrite transformation (DITF). For comparative purposes, two experimental 0.06 wt% C steels were studied: one with 0.03 wt% Nb (Nb steel), and a second with both 0.03 wt% Nb and 0.02 wt% Ti (NbTi steel). Two processing routes were studied. The first was a conventional route, which consisted of a simulated rough deformation schedule with the final roughing pass taking place at 850 °C, which produced fully unrecrystallised austenite grains during deformation with no strain-induced ferrite formation. The second, new, thermomechanical processing route used the same roughing step, after which the steels were reheated at 10 °C/s to a temperature of 1200 °C, isothermally held for 10s allowing for precipitate dissolution, prior to air cooling to a finishing deformation temperature of 850 °C. This route resulted in DIFT primarily on the prior-austenite grain boundaries. The precipitate solution during the reheat treatment increased the supersaturation of Nb and Ti in the austenite matrix on subsequent cooling, which therefore increased the undercooling due to the increased Ae3 . The observation of nanoscale cementite in the DIFT supports the view that it formed through a massive transformation mechanism. The volume fraction of SIP after finish deformation was influenced by the supersaturation of microalloy elements in solution during heat treatment. The new process route led to a significant refinement of the final ferrite grain size. Graphical abstract: